P036: A comprehensive quality improvement initiative to prevent falls in the emergency department. (15th May 2017) - Samuel, P.; Park, J.; Muckle, F.; Lexchin, J.; Mehta, S.; Mcgovern, B.; Chartier, L.B.
Abstract : Introduction: Patients from all population groups visit the emergency department (ED), with increasing visits by elderly patients. Patient falls in the ED are a significant safety concern, and they can lead to serious injuries and worse outcomes. Toronto Western Hospital's ED Quality Improvement (QI) team identified as a problem our assessment and management of patients at risk for falls. The aim of this project was to develop a comprehensive and standardized approach to patients at risk of falls in the ED, including implementing timely interventions for fall prevention.Methods: A literature review of existing tools was completed to develop our own reliable and valid fall risk screening tool for ED patients. QI methods were used to devise a comprehensive strategy starting with detection at triage and implementation of action-driven steps at the bedside, through multiple PDSA cycles, randomized audits, surveys, and education. Repeated measurements were undergone throughout the project, as were staff satisfaction surveys.Results: The chart audits showed a five-fold increase in the completion rate of the fall risk screening tool in the ED by the end of the QI initiative (from 10% to 50%). Constructive feedback by an engaged team of nurses was used to iteratively improve the tool, and there was mostly positive feedback on it after various PDSA cycles were completed. The various component of this novel and useful ED-based falls screening tool and bundle will be presented in tables and figures for other leaders to replicate in their EDs.Conclusion: We developed a completely new ED-specific fall risk screening tool through literature review, front-line provider feedback, and iterative PDSA cycles. It was used for the identification, prevention, and management of ED patients with fall risk. We also contributed to a positive change in the culture of a busy ED environment towards the promotion of patient safety. Education and feedback continue to be provided to the ED nurses for reflective practice, and we hope to continue to improve our tool and to share it with other EDs.